Unethical Practices in Favor of the Organization Analyzed from the Perspective of the Power of Context, Organizations and Individuals - Reynoso Espinoza, Deivit (2023)
The article theoretically addresses the relationship among contextual power, organizations and individuals, and their impact on the adoption and acceptance of unethical practices for the benefit of an organizational entity. The term “gray ethics” is introduced to describe those practices, which are tolerated despite transgressing social norms and, occasionally, legal regulations. This phenomenon is explored from the perspective of the bidirectional influence of these levels of analysis. In an initial instance, the article examines how the organizational context establishes an institutionalized framework that consolidates and facilitates the spread of such practices. Subsequently, it delves into the organization itself, analyzing the roles and functions that influence the choice of these practices in favor of the organization. Finally, it explores the influence exerted by individuals and the forces that guide them, enabling the adoption of these practices. These points are discussed by reviewing relevant research located in academic sources.